Proposed upgrade and new interior scheme of Penang Golden Lounge for Malaysia Airlines at Penang International Airport, 11900 Bayan Lepas, Penang / Ahmad Redza Ihsannuddin - Ihsannuddin, Ahmad Redza (2010)
The project that had been chosen for the final project is proposed upgrade and new interior scheme of Penang Golden Lounge. This proposed Golden Lounge is to provide the occupants the best type of hospitality that the lounge had to offer.